2015
DOI: 10.2131/jts.40.115
|View full text |Cite
|
Sign up to set email alerts
|

Spiroquinazolinone-induced cytotoxicity and apoptosis in K562 human leukemia cells: alteration in expression levels of Bcl-2 and Bax

Abstract: -Spiroquinazolinone compounds have been considered as a new series of potent apoptosis-inducing agents. In this study, anti-proliferative and apoptotic effects of the derivatives from the spiroquinazolinone family were investigated in the human chronic myeloid leukemia K562 cells. The K562 cells were treated with various concentrations of the spiroquinazolinone (10-300 μM) for 3 days and cell viability was determined by MTT growth inhibition assay. 4t-QTC was more active among these compounds with IC50 of 50 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Studies have shown that the death receptor pathway of the mitochondrial pathway is a classic pathway of apoptosis in many tumor cells (16). Bcl-2 and Bax play a key role in the mitochondrial apoptotic pathway (17). In many tumors, including lung cancer, the expression of Bcl-2 is increased in tumors and Bax is decreased (18).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the death receptor pathway of the mitochondrial pathway is a classic pathway of apoptosis in many tumor cells (16). Bcl-2 and Bax play a key role in the mitochondrial apoptotic pathway (17). In many tumors, including lung cancer, the expression of Bcl-2 is increased in tumors and Bax is decreased (18).…”
Section: Discussionmentioning
confidence: 99%
“…Most chemotherapeutic drugs act via stimulating apoptosis of cancer cells. However, toxicity and resistance lead to failure of chemotherapy in CML patients (Ghasemian et al, 2015). For that reason, natural compounds are increasingly considered alternative treatment that has potentials for therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In our present study, the expressions of cleaved caspase-7 and -8 were significantly increased by tanshinone IIA, but there was no change in that of cleaved caspase-9 (Figure 4). Two major molecular pathways that trigger programmed cell death are the caspase-mediated intrinsic pathway, which is induced by cellular stresses, and the extrinsic pathway, which is related to the death receptor [25]. Both pathways activate the apoptotic caspases, resulting in morphological and biochemical cellular alterations related to apoptosis [26].…”
Section: Resultsmentioning
confidence: 99%